Probiotics Bacillus cereus and B. subtilis reshape the intestinal microbiota of Pengze crucian carp (Carassius auratus var. Pengze) fed with high plant protein diets - Li, Jiamin; Fang, Peng; Yi, Xinwen; Kumar, Vikas; Peng, Mo (Frontiers in Nutrition, 2022)
The intestinal dysfunction induced by high plant protein diets is frequently observed in farmed fish, and probiotics of Bacillus genus were documented to benefit the intestinal health through the modulation of intestinal microbiota without clearness in its underlying mechanism yet. Fusobacteria, Proteobacteria, and Firmicutes were observed to be the dominate phyla, but their proportion differentiated in the intestinal bacterial community of Pengze crucian carp (Carassius auratus var. Pengze) fed different diets in this study. Dietary supplementation of B. cereus and B. subtilis could reshape the intestinal bacterial community altered by high plant protein diets through a notable reduction in opportunistic pathogen Aeromonas together with an increase in Romboutsia and/or Clostridium_sensu_stricto from Firmicutes. Due to the alteration in the composition of bacterial community, Pengze crucian carp exhibited characteristic ecological networks dominated by cooperative interactions. Nevertheless, the increase in Aeromonas intensified the competition within bacterial communities and reduced the number of specialists within ecological network, contributing to the microbial dysbiosis induced by high plant protein diets. Two probiotics diets promoted the cooperation within the intestinal bacterial community and increased the number of specialists preferred to module hubs, and then further improved the homeostasis of the intestinal microbiota. Microbial dysbiosis lead to microbial dysfunction, and microbial lipopolysaccharide biosynthesis was observed to be elevated in high plant protein diets due to the increase in Aeromonas, gram-negative microbe. Probiotics B. cereus and B. subtilis restored the microbial function by elevating their amino acid and carbohydrate metabolism together with the promotion in the synthesis of primary and secondary bile acids. These results suggested that dietary supplementation of probiotics B. cereus and B. subtilis could restored the homeostasis and functions of intestinal microbiota in Pengze crucian carp fed high plant protein diets.